L'adaptation de la migration marchande en péninsule Ibérique au xviie siècle : entre résistance, fidélité et stratégie au défi de la frontière - Aurian Meunier (Les Cahiers de Framespa)
While the war was raging in between the French and Spanish monarchies in the second third of the 17th century, trade bans decreed by the Iberian monarchy weakened cross-border trade without hindering it. In the first half of the 17th century, migrant merchants from the Massif Central were the main merchants, peddlers, or agents circulating across the Pyrenees. But new market players or intermediaries appeared and participated in moving around merchandise, legally or illegally, between the two crowns. The objective of this article is to see in what ways the actors of the trans-Pyrenees trade, by the opportunities provided to them and the border circumvention strategies they adopted, managed to transport merchandise on either side of the border.